2021
DOI: 10.3390/genes12121954
|View full text |Cite
|
Sign up to set email alerts
|

The APOE ε4 Allele Affects Cognitive Functions Differently in Carriers of APP Mutations Compared to Carriers of PSEN1 Mutations in Autosomal-Dominant Alzheimer’s Disease

Abstract: Mounting evidence shows that the APOE ε4 allele interferes with cognition in sporadic Alzheimer’s disease. Less is known about APOE in autosomal-dominant Alzheimer’s disease (adAD). The present study explored the effects on cognition associated with the gene–gene interactions between the APOE gene and the APP and PSEN1 genes in adAD. This study includes mutation carriers (MC) and non-carriers (NC) from adAD families with mutations in APP (n = 28 and n = 25; MC and NC, respectively) and PSEN1 (n = 12 and n = 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Recent results from a Swedish population carrying PSEN1 and APP variants related to fAD showed that APOEε4 did not have an effect as a main predictor over cognition, but it did when interacting with other factors. Episodic memory was significantly affected by the interaction between APOEε4 and APP/PSEN1 mutations, showing favorable performance in the absence of APOEε4 in PSEN1 compared to APP mutation carriers [ 175 , 176 ]. Also, interactions between APOEε4 and AoO showed differential effects depending on whether it was APP or PSEN1 mutation carriers; in the first group, verbal abilities and attention were maintained in comparison with those who lacked the APOEε4 allele.…”
Section: The Effect Of Apoementioning
confidence: 99%
See 1 more Smart Citation
“…Recent results from a Swedish population carrying PSEN1 and APP variants related to fAD showed that APOEε4 did not have an effect as a main predictor over cognition, but it did when interacting with other factors. Episodic memory was significantly affected by the interaction between APOEε4 and APP/PSEN1 mutations, showing favorable performance in the absence of APOEε4 in PSEN1 compared to APP mutation carriers [ 175 , 176 ]. Also, interactions between APOEε4 and AoO showed differential effects depending on whether it was APP or PSEN1 mutation carriers; in the first group, verbal abilities and attention were maintained in comparison with those who lacked the APOEε4 allele.…”
Section: The Effect Of Apoementioning
confidence: 99%
“…This demonstrates the existence of an opposite effect of APOEε4 over cognition between EOAD and LOAD patients. Authors have addressed this heterogeneity in disease progression, rate of cognitive decline, and the cognitive domains that are affected in patients with early-onset versus late-onset AD, as well as epistasis or other complex genetic interactions when EOAD is caused by pathogenic mutations [ 175 , 176 ], antagonist pleiotropic effect of APOEε4 heterozygosity over the adult life course [ 177 ], the modulation of educational attainment [ 169 ], or the interaction of environmental factors yet to be discovered. Meanwhile, this heterogeneity in results means that the effect of APOEε4 cannot be or must not be generalized when talking about EOAD.…”
Section: The Effect Of Apoementioning
confidence: 99%
“…In humans, genetic association studies have identified major genetic risk factors for all-cause mortality, including the ε4 allele of the APOE gene ( APOE4 ) 14 . This allele also represents the highest genetic risk factor for late-onset Alzheimer’s disease (AD) as well as the highest genetic risk modifier of early-onset forms of AD 57 . APOE4 may contribute to increased mortality via AD pathologies and AD-independent mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, genetic association studies have identified major genetic risk factors for all-cause mortality, including the ε4 allele of the APOE gene (APOE4) [1][2][3][4] . This allele also represents the highest genetic risk factor for late-onset Alzheimer's disease (AD) as well as the highest genetic risk modifier of early-onset forms of AD [5][6][7] . Emerging human studies implicate APOE4 homozygosity as a major genetic cause, not just a risk modifier, of AD that constitutes one of the most frequent human Mendelian disorders 8 .…”
Section: Introductionmentioning
confidence: 99%
“…A subsequent study of 71 carriers in the same kindred found no effect of APOE e4, but found that the presence of the e2 allele was associated with delayed clinical onset by approximately eight years 6 . Broader investigations including ADAD carriers from multiple families have reported differences between APP and PSEN1 mutations, which may mask APOE effects in combined analyses, but indicate detrimental effects on cognitive performance and decline in PSEN1 carriers 7 , 8 , demonstrating the importance of additional investigation in a large single kindred.…”
Section: Introductionmentioning
confidence: 99%